IMPACT OF TASK-BASED LEARNING ON LEARNER AUTONOMY - Maftuna Abdurasulova (TADQIQOTLAR.UZ, 2024)
This study examines the impact of Task-Based Learning (TBL) on learner autonomy in language education. TBL, an approach that emphasizes using language as a tool for accomplishing meaningful tasks, has been posited to foster greater learner independence by encouraging self-directed learning and critical thinking. This research involved a mixed-methods design, including surveys, interviews, and classroom observations, to assess how TBL influences students' ability to take charge of their learning. The findings indicate that TBL significantly enhances learner autonomy by promoting active engagement, self-regulation, and problem-solving skills. The study concludes with recommendations for integrating TBL strategies to support autonomous learning and suggestions for further research.